Inggris - Adrien Jems Akiles Unitly; Adeleyda M. W. Lumingkewas (Postgraduate, University of Mataram, 2026)
This study aims to evaluate the potential of clove syrup as an antioxidant agent to prevent the decrease in the number of Leydig cells and Sertoli cells in a rat model exposed to cigarette smoke. This study used a randomized controlled trial (CRD), where 18 rats were divided into 6 treatment groups with 3 replications, namely K(N): not given treatment, K(-): a group of rats that were given vitamin C then exposed to cigarette smoke 10 cigarettes/day for 14 days, K(+): A group of rats that were exposed to cigarette smoke 10 cigarettes/day for 14 days, and a group of rats that were given clove syrup 1.28ml (P1), clove syrup 2.56ml (P2), clove syrup 3.84ml (P3) then exposed to cigarette smoke 10 cigarettes/day for 14 days. After the rat were treated and necropsied, the testes were taken for HE staining. Leydig cells and Sertoli cells were counted, and the data were analyzed using ANOVA. The results were then further analyzed using the Duncan test (α=0.05) in SAS, followed by the smallest significant difference test. The results of the study showed that clove syrup has antioxidant activity in protecting the number of Leydig cells and Sertoli cells.